A Single β-Amino Acid Substitution to Angiotensin II Confers AT 2 Receptor Selectivity and Vascular Function - Emma S. Jones; Mark P. Del Borgo; Julian F. Kirsch; Daniel Clayton; Sanja Bosnyak; Iresha Welungoda; Nicholas Hausler; Sharon Unabia; Patrick Perlmutter; Walter G. Thomas; Marie‐Isabel Aguilar; Robert E. Widdop (2011)
Novel AT(2)R ligands were designed by substituting individual β-amino acid in the sequence of the native ligand angiotensin II (Ang II). Relative ATR selectivity and functional vascular assays (in vitro AT(2)R-mediated vasorelaxation and in vivo vasodepressor action) were determined. In competition binding experiments using either AT(1)R- or AT(2)R- transfected HEK-293 cells, only β-Asp(1)-Ang II and Ang II fully displaced [(125)I]-Ang II from AT(1)R. In contrast, β-substitutions at each position of Ang II exhibited AT(2)R affinity, with β-Tyr(4)-Ang II and β-Ile(5)-Ang II exhibiting ≈ 1000-fold AT(2)R selectivity. In mouse aortic rings, β-Tyr(4)-Ang II and β-Ile(5)-Ang II evoked vasorelaxation that was sensitive to blockade by the AT(2)R antagonist PD123319 and the nitric oxide synthase inhibitor L-NAME. When tested with a low level of AT(1)R blockade, β-Ile(5)-Ang II (15 pmol/kg per minute IV for 4 hours) reduced blood pressure (BP) in conscious spontaneously hypertensive rats (β-Ile(5)-Ang II plus candesartan, -24 ± 4 mm Hg) to a greater extent than candesartan alone (-11 ± 3 mm Hg, n=7, P<0.05), an effect that was abolished by concomitant PD123319 infusion. However, in an identical experimental protocol, β-Tyr(4)-Ang II had no influence on BP (n=10), and it was less stable than β-Ile(5)-Ang II in plasma stability assays. Thus, this study demonstrated that a single β-amino acid substitution resulted in a compound that demonstrated both in vitro vasorelaxation and in vivo depressor activity via AT(2)R. This approach to the design and synthesis of novel AT(2)R-selective peptidomimetics shows great potential to provide insight into AT(2)R function.